Learners’ Anxiety and Their Perceptions Toward Oral Corrective Feedback in ESP-Speaking Class - Roro Millatu Al Ghaniy; Mirjam Anugerahwati (Jurnal Pendidikan Humaniora, 2022)
Abstract: This research aimed at investigating learners’ anxiety levels and perceptions toward Oral Corrective Feedback (OCF) in ESP-Speaking class. Survey research design was used to investigate ESP learners’ anxiety levels and their perceptions toward OCF. One hundred and forty one learners were involved as the research participants. Furthermore, two closed-ended questionnaires namely Foreign Language Classrooms Anxiety Scale (FLCAS) and the learners’ perceptions toward OCF were used to collect the data. The findings of this study revealed that majority of nursing learners experienced moderate anxiety level. Furthermore, majority of the learners, regardless their anxiety, perceived OCF positively.Abstrak: Penelitian ini bertujuan untuk meneliti tingkat kecemasan dan persepsi mahasiswa terhadap Masukan Korektif Lisan (OCF) di kelas ESP-Speaking. Seratus empat puluh satu mahasiswa semester dua keperawatan dilibatkan sebagai partisipan penelitian. Selanjutnya, dua kuesioner yaitu Foreign Language Classrooms Anxiety Scale (FLCAS) dan persepsi mahasiswa ESP terhadap OCF digunakan sebagai instrumen penelitian. Hasil penelitian ini menunjukkan bahwa mayoritas mahasiswa keperawatan mengalami tingkat kecemasan sedang (44 persen) di kelas ESP-Speaking. Terkait dengan persepsi terhadap corrective feedback lisan, mahasiswa. sepenuhnya mendukung pemberian corrective feedback lisan.